IMPLEMENTASI TRI HITA KARANA DI OBJEK WISATA ALAS KEDATON UPAYA PELETARIAN LINGKUNGAN WISATA - Ni Kade Seri Andayani (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
Alas Kedaton tourism object is one of the tourist destinations known for its natural beauty and the presence of monkeys which are the main attraction, becoming a cultural tourism object, Alas Kedaton is very closely related to Hindu culture. Of course, it cannot be separated from religious rituals and various religious philosophies such as tri Hita Karana which is implemented in the social life of the local community both in management (managers and traders) towards visitors, towards the environment and respecting the heritage of religious ceremonies at Alas Kedaton Temple. This study uses qualitative methods, the data sources are primary and secondary. Data collection techniques include observation techniques, interviews, literature and documentation, as well as techniques for determining informants. The implementation of the Tri Hita Karana teachings at the Alas Kedaton tourist attraction has been going quite well, this can be seen where the relationship between humans and God has been established in every piodalan taking place, the relationship between managers and visitors is considered good enough because the managers always provide comfortable service and provide a sense of security for guests, the manager's relationship with the environment has also been harmonious, this can be seen from the developments both in garden planning, reforestation/reforestation and in feeding the monkeys.